Vortex dynamics in Bi2Sr2CaCu2O8+δ single crystals with planar defects - Herbsommer, J.A. (2001)
Fil: Herbsommer, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina